THE STANDARD OF CHORAL SOUND IN THE PERFORMANCE INTERPRETATION OF UKRAINIAN SACRED MUSIC - Anastasiia Pater (International Journal of Innovative Technologies in Social Science, 2020)
The article highlights the issue of achieving a sound standard in the performance interpretation of sacred music by Ukrainian choral groups, which is relevant in the process of understanding the intonation-figurative sphere of performance. We believe that the standard performance version is the performance embodiment of a musical work that corresponds to the sound ideals characteristic of a certain tradition. The sound standard covers a complex of aesthetic and performing means that form a system of physiologically-technological technical-virtuosic, artistic-aesthetic components of the reference sound. Based on the analysis of the choral concert of Maxim Berezovsky "Don’t reject me in my old age" in the performance versions of the Lviv state academic men’s choral Capella "Dudarik" (conductor – Nikolay Katsal) and the Kiev chamber choir named after B. Lyatoshinsky (conductor – Viktor Ikonnik), the measure of compliance of their performance with the standard parameters of sound is traced. In the performance skills of both groups, the ability to reinterpret a musical work in accordance with its verbal basis can be traced. Depending on the figurative content, a rational reserved approach is used, devoid of emotional sound expression, or, in another situation, the secrets of spiritual experiences are soulfully transmitted. This mobility in the sense of the laws of eternal beauty and the ability to embody them in choral sonority, the combination of properties of the conscious and unconscious, determine the features of performing thinking inherent in the Ukrainian national choral art. The performance of the choral Capella "dudarik" truthfully conveys the performance style of the XVIII century, in which M. Berezovsky created. The combination of high light trebles, timbre- free soft Altos, ringing tenor groups and deep basses creates an impression of directness and sincerity in the transmission of spiritual content. But the choral intonation of the Kiev chamber choir appeals to the Western European style of music making, which is characterized by the most accurate reproduction of the elements of articulation specified in the composer’s text – strokes, accents, caesuras, dynamic palette. At the same time, the balance of the single timbre ensemble of the choir with the deep "heart" sound paint characteristic of the Ukrainian tradition is preserved. The interpretation of musical architectonics by both groups brings its own uniqueness to their performing style and image-sound paint – and this is the ability to perceive and report the living matter of the work, to reincarnate the essential meanings of the national spiritual and aesthetic experience. Each of the considered performance versions corresponds to the essential characteristics of the reference sound.